Communicating livestock feed and forage innovations - Mesfin, Hailemariam (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Presentation in Media Training Workshop on Climate Smart Livestock Feed and Forage Innovations. Addis Ababa, Ethiopia.